Applications of Partial Differential Equations - Wong, Patricia J. Y. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Partial differential equations are indispensable for modeling various phenomena and processes, such as those in physics, biology, finance, and engineering. Finding solutions to partial differential equations using qualitative theories or quantitative methods, as well as the application of such investigations to real-world problems, has drawn a large amount of interest from researchers. This reprint encompasses all the articles that were accepted and published in this Special Issue titled "Applications of Partial Differential Equations ". We hope that these accepted and published papers will be impactful and motivate future research on partial differential equations for solving complex problems in various fields, disciplines, and applications.